Achieving Chinese Carbon Neutrality Based on Water–Temperature–Radiation–Land Coupling Use - Tian, Yinglin; Xie, Di; Li, Tiejian; Li, Jiaye; Zhang, Yu; Jing, Huan; Zhong, Deyu; Wang, Guangqian (Frontiers in Environmental Science, 2021)
Facing irreversible and catastrophic changes on the earth, China has committed to peak the net carbon emission by 2030 and to achieve carbon neutrality by 2060. The pledge requires significant mitigation immediately and sustainably. Under this background, some perspectives are given in this paper based on the comprehensive use of natural resources. First, utilizing the STIRPAT (Stochastic Impacts by Regression on Population, Affluence, and Technology) model and statistical data, net carbon emissions of provinces in China are anticipated, which lays a foundation for the further “three-step” carbon neutralization route. Second, a strategy of water-temperature-radiation-land coupling use is proposed, considering 1) the carbon emission cut, which relies on comparing the energy intensity and energy structure in China with those in developed countries; 2) the carbon sink increase, which depends on the evaluation of constraints of hydrometeorological factors on ecological productivity. Finally, the necessity and possibility of carbon trading and redistribution of the climate resources are discussed to ensure that China's national net carbon emission would be reduced to zero by 2060.